ESG AND PROFITABILITY: THE MODERATING OF LEVERAGE IN THE INDONESIAN ENERGY SECTOR - Ida, Ida; Tjandrasa, Benny Budiawan; Setyawan, Surya (Jurnal Muara Ilmu Ekonomi dan Bisnis, 2025)
Sektor energi di Indonesia menghadapi dinamika dan tantangan kompleks seperti dampak lingkungan, kebutuhan investasi untuk infrastruktur, tekanan transisi energi, dan regulasi yang ketat. Penerapan ESG  menjadi penting sebagai salah satu strategi keberlanjutan perusahaan. Namun, belum banyak studi yang mengkaji bagaimana ESG berkontribusi terhadap profitabilitas perusahaan energi, terutama dalam interaksinya dengan struktur keuangan. Penelitian ini bertujuan untuk menganalisis pengaruh skor ESG, Debt to Equity Ratio (DER), Current Ratio (CR) terhadap profitabilitas yang diukur dengan Return on Asset (ROA) pada perusahaan sektor energi yang terdaftar di Bursa Efek Indonesia (BEI), serta peran moderasi dalam hubungan antara ESG dan ROA. Dengan pendekatan kuantitatif kausal, penelitian ini menggunakan Teknik pengambilan sampling purposive sampling dengan menggunakan lima perusahaaan sektor energi yang terdaftar sebelum tahun 2015 dan memiliki data ESG dan laporankeuangan lengkap selama periode 2015-2024. Analisis data menggunakan regresi data panel dan hasil penelitian menunjukkan bahwa Common Effect Model merupakan model yang tepat dalam penelitian ini dan hasil pengujian menunjukkan bahwa ESG, DER, dan CR berpengaruh positif signifikan terhadap profitabilitas dan leverage yang diukur dengan DER terbukti memoderasi secara negative pengaruh ESG terhadap profitabilitas. Kesimpulan dari studi ini menekankan pentingnya pengelolaan struktur modal agar implementasi ESG dapat memberikan nilai tambah optimal bagi kinerja keuangan perusahaan. Implikasi praktisnya, perusahaan energi perlu menyeimbangkan komitmen keberlanjutan dengan strategi keuangan yang sehat. Keterbatasan penelitian ini terletak pada cakupan sektor dan variabel yang digunakan, sehingga studi lanjutan disarankan untuk memperluas sektor industri dan mempertimbangkan variabel penjelas lainnya guna memperkaya pemahaman tentang dinamika ESG dan profitabilitas   The energy sector in Indonesia has a lot of complicated challenges for business, such as regulatory requirements, infrastructure investment, environmental effects, and pressures from the energy transition. Environmental, social, and governance (ESG) practices ought to be given top priority in corporate sustainability plans. The relationship between ESG and profitability, however, has not received much attention in research, especially when it comes to the role as a mediating factor in energy companies. This study analyzes the role of DER as a moderating variable of the effect of ESG on ROA, the direct effect of ESG, DER, and CR on the profitability of energy sector companies listed on the IDX. The purposive sampling technique is used in this quantitative & causal research by obtaining a sample of five energy sector companies that have published a complete financial report for the year 2015-2014, an ESG score, and were listed on the IDX before 2015. The results of the panel data regression test found that DER, CR, and ESG had a meaningful effect on profitability. This shows that the capital structure of the company should be managed to support and optimize the implementation of ESG to create added value for the company's profitability. The practical implications of this study suggest that an equilibrium should be achieved between corporate financial performance and corporate sustainability commitment. Further research should be carried out to investigate various other sectors and other variables. The main limitations of this study are the sector and the variables considered in this study.This study analyzes the role of DER as a moderating variable of the effect of ESG on ROA, the direct effect of ESG, DER, and CR on the profitability of energy sector companies listed on the IDX. The purposive sampling technique is used in this quantitative & causal research by obtaining a sample of five energy sector companies that have published a complete financial report for the year 2015-2014, an ESG score, and were listed on the IDX before 2015. The results of the panel data regression test found that DER, CR, and ESG had a meaningful effect on profitability. This shows that the capital structure of the company should be managed to support and optimize the implementation of ESG to create added value for the company's profitability. The practical implications of this study suggest that an equilibrium should be achieved between corporate financial performance and corporate sustainability commitment. Further research should be carried out to investigate various other sectors and other variables. The main limitations of this study are the sector and the variables considered in this study.